Feed Intake and Nutrient Digestibility, Rumen Fermentation Profiles, Milk Yield and Compositions of Lactating Dairy Cows Supplemented by Flemingia macrophylla Pellet - B. Phesatcha; K. Phesatcha; B. Viennasay; N. T. Thao; M. Wanapat (Tropical Animal Science Journal, 2021)
Feed intake and nutrient digestibility, rumen fermentation profiles, milk yield and compositions of lactating dairy cows fed with Flemingia macrophylla pellet (FMP) were evaluated. Four crossbred dairy cows in early lactation were randomly allocated into a 2×2 factorial arrangement in a 4×4 Latin square design (LSD). The first factor was protein level of concentrate mixtures consisted of two levels, i.e., 14% and 16%. The second factor was supplementation levels of FMP consisted of two levels, i.e., 0 and 150 g/cow/d. There were no interactions between the protein level of concentrate and FMP supplementation on feed intake and digestibility, rumen fermentation profiles, milk yield and composition of lactating dairy cows. The findings revealed that both factors significantly impacted feed intakes. They also significantly increased the digestibility of CP and neutral detergent fiber (NDF). Ruminal ammonia nitrogen and propionate (C3) concentrations were improved (p<0.05), while rumen acetate (C2), the ratio of C2:C3, estimated methane (CH4) production, and protozoal counts were subsequently reduced (p<0.05). Crude protein level and FMP supplementation additionally improved nitrogen absorption and utilization, as well as microbial nitrogen synthesis. Milk production was significantly increased by the FMP feeding. In conclusion, a concentrated mixture with 16% CP along with supplementation of FMP at a dose of 150 g/cow/d could significantly increase rumen fermentation end-products, microbial protein synthesis, mitigated rumen CH4 production, and milk production in lactating dairy cows fed with rice straw.